Chemical analysis of mercury in fresh fish in some of the main rivers of Roraima by the atomic fluorescence spectrometry method (AFS) - Mesquita, Gabrielly Vieira (2023)
Roraima has a high demand for fish consumption and one of the major concerns is regarding the bioaccumulation of mercury in fish that are used for human consumption, due to its toxic potential. This article aimed to analyze mercury levels in fresh fish samples collected in rivers located in the state of Roraima, using the Atomic Fluorescence Spectrometry (AFS) technique, with 44 fish samples of different species being collected. The samples were collected in the Uraricoera, Branco (at three different points) and Mucajaí (at two points) rivers. it is noted that some samples gave approximate values ​​of the limits allowed by the Ministry of Health, but the Hg contents are within the values ​​indicated and allowed by the Ministry of Health, which establishes the value of 500 (ng/g) of Hg allowed for non-predatory fish , in predatory fish, this value is up to 1000 (ng/g).Although the contents are within the limits established and allowed by the Ministry of Health, it is necessary to carry out constant monitoring to assess the impact of mining on human health.